Radix Rehmanniae Praeparata (Shu Dihuang) exerts neuroprotective effects on ICV-STZ-induced Alzheimer's disease mice through modulation of INSR/IRS-1/AKT/GSK-3β signaling pathway and intestinal microbiota - Yunfang Su; Yunfang Su; Ningning Liu; Ruiqin Sun; Jinlian Ma; Zhonghua Li; Pan Wang; Huifen Ma; Yiran Sun; Junying Song; Zhenqiang Zhang (Frontiers Media S.A., 2023)
Radix Rehmanniae Praeparata (RRP, Shu Dihuang in Cinese) is widely used as primal medicine in Chinese herbal formula for the treatment of Alzheimer's disease (AD). However, the underlying mechanism of RRP for AD remains unclear. The aim of this study was to investigate the therapeutic effect of RRP on intracerebroventricular injection of streptozotocin (ICV-STZ)-induced AD model mice and its potential mechanism. ICV-STZ mice were continuously gavaged with RRP for 21 days. The pharmacological effects of RRP were evaluated by behavioral tests, brain tissue H&E staining and hippocampal tau protein phosphorylation levels. The expression levels of insulin receptor (INSR), IRS-1, pSer473-AKT/AKT and pSer9-GSK-3β/GSK-3β proteins in hippocampal and cortical tissues were detected by Western-blot method. The 16S rRNA gene sequencing was used to analyze the changes of intestinal microbiota in mice. The compounds in RRP were analyzed by mass spectrometry and their binding ability to INSR proteins was detected by molecular docking. The results showed that RRP ameliorated cognitive dysfunction and neuronal pathological changes of brain tissue in ICV-STZ mice, reduced tau protein hyperphosphorylation, INSR, IRS-1, pSer473-AKT/AKT, and pSer9-GSK-3β/GSK-3β levels in hippocampal and cortical tissues. Meanwhile, RRP reversed ICV-STZ-induced dysregulation of intestinal microbiota in AD mice. Mass spectrometry analysis showed that the RRP consisted mainly of seven compounds, namely Acteoside (Verbascoside), 5-Hydroxymethyl-2-furaldehyde (5-HMF), Apigenin7-O-glucuronide, Icariin, Gallic acid, Quercetin-3β-D-glucoside, and Geniposide. Molecular docking results further indicated that the compounds in RRP have binding ability to INSR protein and potential multiple synergistic effects. RRP ameliorates cognitive dysfunction and brain histopathological changes in AD mice. The mechanism of RRP ameliorating AD may be related to the regulation of INSR/IRS-1/AKT/GSK-3β signaling pathway and intestinal microbiota. This study supports the potential anti-AD efficacy of RRP and initially reveals the pharmacological mechanism of RRP, providing a theoretical basis for further clinical application of RRP.